Comparison of clinical characteristics between patients with microvascular and epicardial coronary artery spasm. (25th November 2020) - Kato, K; Tateishi, K; Saito, Y; Kitahara, H; Fujimoto, Y; Kobayashi, Y
Abstract: Background: Coronary functional abnormalities including both epicardial and microvascular coronary artery spasm represent an important role responsible for myocardial ischemia in patients with angina and nonobstructive coronary artery disease. However, clinical characteristics associated with microvascular spasm (MVS) have not been fully evaluated. Purpose: The aim of this study was to assess differences in clinical features between patients with MVS and epicardial coronary spasm. Methods: A total of 732 consecutive patients with suspected angina who presented nonobstructive coronary arteries and underwent intracoronary acetylcholine provocation test were retrospectively enrolled in this study. Epicardial coronary spasm was defined as total or subtotal occlusion of epicardial coronary arteries accompanied by chest pain and/or ischemic electrocardiographic changes in response to acetylcholine provocation test. MVS was diagnosed when chest pain and/or ischemic electrocardiographic changes developed after administration of acetylcholine in the absence of epicardial coronary spasm. Clinical characteristics were compared between patients with MVS and epicardial coronary spasm. Results: Of all patients, 83 patients (11%) had MVS, 367 (50%) had epicardial coronary spasm, and the other patients (39%) showed neither MVS nor epicardial coronary spasm. Patients with MVS tended to be older (65.6±12.7 vs. 63.0±12.3 years, P=0.088) and were more frequently female (60.2% vs. 41.1%, P=0.0016) in comparison with patients with epicardial coronary spasm. Patients with MVS were less likely to be smokers (8.6% vs. 22.9%, P=0.0018), while there were no significant differences in the other coronary risk factors such as hypertension, dyslipidemia, and diabetes mellitus. Serum uric acid were significantly lower in patients with MVS (4.9±1.1 vs. 5.4±1.3 mg/dl, P=0.0018). Conclusion: Our study demonstrated that patients with MVS had distinctive clinical background from those with epicardial coronary spasm, suggesting different mechanisms may involve the development of MVS. Funding Acknowledgement: Type of funding source: None